Behçet’s Disease: a systemic case with recurrent oral ulcers - Anjos, Evandro Barbosa dos; Freitas, Edimilson Martins de; Martelli, Daniella Reis Barbosa; Dias, Verônica Oliveira; Machado, Renato Assis; Anjos, Jamile Pereira Dias dos; Martelli-Júnior, Hercílio (Journal of Oral Diagnosis, 2016)
Behçet’s disease is a chronic multisystem inflammatory disorder of unknown etiology and characterized mainly by recurrent oral ulcers, ocular involvement, genital ulcers, and skin lesions, presenting with remissions and exacerbations. Case report: The case report presents a patient with recurrent oral ulcers history and extracutaneous ulcers to 10 years who was diagnosed as having Behçet’s disease and was successfully treated. Discussion: Although complications involving the gastrointestinal, cardiovascular, renal, pulmonary, urological, artery, and central nervous system can be observed, some patients can remain asymptomatic for a long period after the diagnosis. Conclusion: This report emphasises that systemic diseases, including Behçet’s disease, can have variable presentations and can be frequently misdiagnosed.